2017
DOI: 10.1186/s12867-017-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin T from sea bass (Dicentrarchus labrax L.): molecular characterization, tissue localization and expression after nodavirus infection

Abstract: BackgroundImmunoglobulins (Igs) are fundamental components of the adaptive immune system of vertebrates, with the IgT/IgZ isotype specific of Teleosts. In this paper we describe the identification of an IgT heavy chain from the European sea bass (Dicentrarchus labrax L.), its molecular characterization and tissue mRNA localization by in situ hybridization.ResultsSea bass IgT consists of 552 aa (Accession Number KM410929) and it contains a putative 19 amino acids long signal peptide and one potential N-glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 59 publications
1
34
0
1
Order By: Relevance
“…Here, we sought to study the response of D. labrax to infection by NNV, one of the most threatening pathogens in the culture of this important commercial fish species. Some previous studies have revealed the overexpression of certain immune genes after in vivo or in vitro infection with NNV in both European sea bass [14][15][16][17][18][19][20][21][22] and other fish species [5, 6, 8, 10-13, 20, 34], but the present study is the first to conduct RNA-Seq in D. labrax after in vivo infection with NNV.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Here, we sought to study the response of D. labrax to infection by NNV, one of the most threatening pathogens in the culture of this important commercial fish species. Some previous studies have revealed the overexpression of certain immune genes after in vivo or in vitro infection with NNV in both European sea bass [14][15][16][17][18][19][20][21][22] and other fish species [5, 6, 8, 10-13, 20, 34], but the present study is the first to conduct RNA-Seq in D. labrax after in vivo infection with NNV.…”
Section: Discussionmentioning
confidence: 86%
“…It has been previously suggested that the adaptive immune response is critical in the defence against NNV, even at early times post-infection [22,[43][44][45]. Considering this suggestion and the observed overexpression of the genes involved in cortisol synthesis in the head kidney, we further investigated whether cortisol overload increases the susceptibility of European sea bass to NNV.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Besides innate and cell mediated immunity, humoral immunity also plays an important role in protecting fish against nodavirus infection ( Chen et al, 2014 ), especially the two immunoglobulins, IgM and IgT. Infection of susceptible seabass with low titer of nodavirus did not significantly alter the expression of IgM and IgT in the gills and spleen ( Buonocore et al, 2017 ) but only induced a marginal increase of serum IgM ( Scapigliati et al, 2010 ). On the other hand, activation of IgM + and IgT + B cells in the brain and overexpression of soluble IgT + by B cells in the head kidney by early inflammatory response in the central nervous system reduced nodaviral replication in the resistant aquaculture-relevant fish species ( Lopez-Munoz et al, 2012 ; Piazzon et al, 2016 ).…”
Section: Survey Methodsologymentioning
confidence: 99%
“…Manuscript to be reviewed immunoglobulins, IgM and IgT. Infection of susceptible seabass with low titer of nodavirus did not significantly alter the expression of IgM and IgT in the gills and spleen (Buonocore et al, 2017) but only induced a marginal increase of serum IgM (Scapigliati et al, 2010). On the other hand, activation of IgM + and IgT + B cells in the brain and overexpression of soluble IgT + by B cells in the head kidney by early inflammatory response in the central nervous system reduced nodaviral replication in the resistant aquaculture-relevant fish species (Lopez-Munoz, 2012;Piazzon et al, 2016).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%